A Knowledge‐Based Approach to Public Value Management: A Case Study of Change Implementation in Disability Services in Western Australia. Issue 2 (5th June 2018) - Soo, Christine; Chen, Shannon; Edwards, Mark G.
Abstract: This paper provides a knowledge‐based perspective to understanding public value management (PVM). As distinct from other approaches to public administration, PVM focuses on collaborative capacity building for the creation of public value. To develop the notion of PVM further, we explore the role of a knowledge‐based strategy in a case study of change implementation in 18 disability service organisations in Western Australia. Our findings show important inter‐relationships between knowledge management strategy, adopting a person‐centred approach to service provision, and sustainability of change implementation. We discuss the implications of the study for disability sector change management and for the further exploration of the strategic role of knowledge management capabilities in the study and practice of PVM in public sector administration. The paper explores the relationship between an organisation's knowledge capture and sharing systems and processes and its ability to implement change in a way that generates long‐term benefits for both public sector employees (e.g., engaging with key stakeholders to generate innovative solutions for serving client needs) and clients (i.e., increased well‐being through better service design and support). Abstract : The article explores the relationship between an organisation's knowledge capture and sharing systems and processes and its ability to implement change in a way that generates long‐term benefits for both public sector employees (e.g., engaging with key stakeholders to generate innovative solutions for serving client needs) and clients (i.e., increased well‐being through better service design and support).